Analisis Pelayanan Pengurusan Administrasi Kartu Keluarga (KK) di Kantor Desa Ngaglik Kecamatan Srengat Kabupaten Blitar - Elsa Santi; Muhammad Nasyiruddin; Hanik Amaria (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study aims to find out the process of Family Card (KK) administration services and identify the obstacles faced in its implementation at the Ngaglik Village Office, Serengat District, Blitar Regency. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The research subjects consisted of village staff and communities who had managed KK, who were selected by purposive sampling. Data analysis is carried out through three main stages, namely data reduction, data presentation, and conclusion drawn. The results of the study show that the administrative services of the family at the Ngaglik Village Office have been running quite optimally. This is shown by the existence of clear service procedures, good officer responsiveness, and the implementation of a digital system in the administrative process. However, there are still several obstacles that hinder the effectiveness of services, including the lack of initial information received by the applicant, the slow response of communication through digital media, and the limitation of supporting facilities such as technology devices and adequate service spaces. These findings show the need to increase service capacity through strengthening information systems, officer training, and providing more representative support facilities. This research is expected to be an input for the village government in developing administrative services that are more efficient, transparent, and responsive to the needs of the community.